Healthy Food as a New Technology—The Implications of Technological Diffusion and Food Price for Changes in Eating Habits - Dohmen, Anne E.; Raman, D. Raj (Frontiers in Nutrition, 2018)
Diet influences health and poor diets drive up healthcare costs for individuals and society as a whole. Multiple governmental programs in the US have aimed to educate citizens about diet choices, resulting in documented successes as well as unintended consequences such as increased food waste. Here we examine some of the relationships between healthy diets, food prices, and wealth, by drawing parallels between the diffusion of technological innovation and healthy food diets. We introduce a simple modelling framework to estimate the adoption rates of healthy diets based on income and food prices, and describe the implications of the modelling results for the food industry and for government.